Clinica/ bioethics. The problem of the patiem with chronic obstntctive bronchitis. - Furfori, P. A.; Pala, F.; Messina, M. (Medicina e Morale, 1994)
The public believes that resuscitation and intensive care are more probably guilty of a lack of humanity and the authors believe that it is possible to talk about humanization of these subjects by illustrating two clinical cases of patients with chronic respiratory insufficiency and by drawing the ethical consequences. In these situations the ethical problems raised would be the following: the principle of the autonomy of the patient, who sometimes, because of his condition, is unable to give serene and conscious consent; the principle of truth, to gauge according to the person's psychological characteristics; the freedom-responsibility of the relatives; the principle of beneficience-non maleficience, which should be carefully evaluated in this case. Possible guidelines are worked out, keeping in mind each patient's particular characteristics: the promotion of the physical and social development of the person; the priority of the respect for physical life; the respect for the dignity of the person; the right, when possible, to the patient's informed consent, providing the relatives with information too; not to begin a treatment if it is considered useless and the patient has not agreed to it, if possible. Finally the authors believe that, in the light of the above conside rations, there are two ways to achieve the humanization of the assistance for the patient with chronic obstructive bronchopathy (BPCO): in the case of the pa tients' screening with BPCO at the initial phase, it is possible, together with the relatives and the family doctor, to work out the strategy to be followed in case the pathology becomes acute. In the other case, that is, when the patient arrives to the attention of the physician unconscious or in an acute pbase, it is important to humanize the stay in resuscitation as much as possible.